A Stochastic Approach for Determining Profit Rate of Islamic Financing Products - Isa, Zaidi; Shafie, Nur Amalina (International Journal of Economics and Financial Issues, 2017)
Islamic Bank in Malaysia uses Bai’ Bithaman Ajil (BBA) method and Musharakah Mutanaqisah Partnership (MMP) method for the home financing process. However, these house price calculation methods are still similar to conventional computation. In addition, profit rate in the Islamic bank still refer interest rate as benchmark. The objective in this study is to determine a profit benchmark by using stochastic forecasting. Base Financing Rate (BFR) data from the year 1999 until 2014 is used in this study to forecast a profit for home financing and to find an optimum price. The Exponential Brownian Motion Model with drift is one of the stochastic forecasting models which has been identified as the best model to forecast the data in this study. After that, the probability of profit is compared to choose the best profit. The median of a profit distribution is proposed as a benchmark for determining the house price. This propose benchmark is fair to both bank and customer in terms of profit and installment, respectively. Keywords: forecasting, risk, analysis JEL Classifications: G170